Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1097/md.0000000000013568
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical activity and stroke in a middle-aged and elderly Chinese population

Abstract: Background:Accumulating evidence has reported that physical activity (PA) is effective in reducing stroke and mortality. However, whether PA levels are associated with stroke in middle-aged and elderly people in Jiangxi Province of China remains unclear. In the present study, we evaluated the association between PA and the risk of stroke in Jiangxi Province of China.Methods:A cross-sectional survey was conducted in Jiangxi Province of China from November 2013 to August 2014, using standardized questionnaire fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
2
11
1
Order By: Relevance
“…A study showed that a high or moderate level of PA was protective against stroke in men not women [ 13 ]. In addition, a study found that vigorous physical activity (VPA) was associated with a lower chance of having a stroke compared with light physical activity (LPA) [ 14 ], whereas other research has shown that VPA did not decrease the risk of stroke [ 15 ]. Meanwhile, there were also some inconsistent results in several studies about the associations between the frequency of PA and the risk of stroke [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that a high or moderate level of PA was protective against stroke in men not women [ 13 ]. In addition, a study found that vigorous physical activity (VPA) was associated with a lower chance of having a stroke compared with light physical activity (LPA) [ 14 ], whereas other research has shown that VPA did not decrease the risk of stroke [ 15 ]. Meanwhile, there were also some inconsistent results in several studies about the associations between the frequency of PA and the risk of stroke [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, proper educational programs for PA engagement interventions, adequate facilities, and personnel for exercise guidance for nursing home residents are needed. Previous studies conducted in China showed that vigorous PA, compared with low and moderate PA, was associated with a lower risk of stroke in elderly people [2]. Findings from Underwood et al [25] also suggested that a moderateintensity exercise program did not reduce depressive symptoms among residents of care homes.…”
Section: Discussionmentioning
confidence: 93%
“…Poor PA leads to insufficient energy expenditure, which results in obesity and chronic diseases like type 2 diabetes and cardiovascular diseases [1]. PA is essential for healthy aging and offers many health benefits, including reduced risk of chronic diseases [2] and premature death [3].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, proper educational programs for PA engagement interventions, adequate facilities, and personnel to provide exercise guidance for nursing home residents are needed. Previous studies conducted in China showed that vigorous PA, compared with low and moderate PA, was associated with a lower risk of stroke in elderly people [ 2 ]. Findings from Underwood et al [ 40 ] also suggested that a moderate-intensity exercise program did not reduce depressive symptoms among residents of care homes.…”
Section: Discussionmentioning
confidence: 99%
“…Poor PA leads to insufficient energy expenditure, which results in obesity and chronic diseases like type 2 diabetes and cardiovascular diseases [ 1 ]. PA is essential for healthy aging and offers many health benefits, including a reduced risk of chronic diseases [ 2 ] and premature death [ 3 ]. Moreover, the implementation of a PA program improves physical [ 4 ] and cognitive functions [ 5 , 6 ], increases the quality of life, and decreases depressive symptoms [ 7 ] in elderly adults.…”
Section: Introductionmentioning
confidence: 99%